2022
DOI: 10.3389/fcell.2022.918970
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new member of Mortaparib class of inhibitors that target mortalin and PARP1

Abstract: Mortalin, a heat shock family protein enriched in cancer cells, is known to inactivate tumor suppressor protein p53. Abrogation of mortalin-p53 interaction and reactivation of p53 has been shown to trigger growth arrest/apoptosis in cancer cells and hence, suggested to be useful in cancer therapy. In this premise, we earlier screened a chemical library to identify potential disruptors of mortalin-p53 interaction, and reported two novel synthetic small molecules (5-[1-(4-methoxyphenyl) (1,2,3,4-tetraazol-5-yl)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 86 publications
4
9
0
Order By: Relevance
“…The long-term (2 weeks) effect, as examined by colony forming assay, showed a decrease in clonogenicity in Mortaparib Mild -treated cells (~15, 30, and 40% in Saos2 and ~20, 40, and 55% in SKOV3 with 1, 2.5, and 5 μM Mortaparib Mild , respectively ( Figure 1 C)). These data suggested that Mortaparib Mild is effective for p53-null cancer cells in addition to its p53-dependent cytotoxicity in p53 wild-type cancer cells [ 28 ]. We investigated the mechanism of its cytotoxicity in p53-null cells as follows.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The long-term (2 weeks) effect, as examined by colony forming assay, showed a decrease in clonogenicity in Mortaparib Mild -treated cells (~15, 30, and 40% in Saos2 and ~20, 40, and 55% in SKOV3 with 1, 2.5, and 5 μM Mortaparib Mild , respectively ( Figure 1 C)). These data suggested that Mortaparib Mild is effective for p53-null cancer cells in addition to its p53-dependent cytotoxicity in p53 wild-type cancer cells [ 28 ]. We investigated the mechanism of its cytotoxicity in p53-null cells as follows.…”
Section: Resultsmentioning
confidence: 99%
“…Mortaparib (5-[1-(4-methoxyphenyl)(1,2,3,4-tetraazol-5-yl)]-4-phenylpyrimidine-2-ylamine) [ 25 ], Mortaparib Plus (4-[(1E)-2-(2-phenylindol-3-yl)-1-azavinyl]-1,2,4-triazole) [ 26 , 27 ], and Mortaparib Mild (4-[(4-amino-5-thiophen-2-yl-1,2,4-triazol-3-yl)sulfanylmethyl]-N-(4-methoxyphenyl)-1,3-thiazol-2-amine) [ 28 ] were purchased from NAMIKI SHOJI Co., Ltd. (Shinjuku, Japan). Stock solutions (50 mM) were prepared in Dimethyl Sulfoxide (DMSO) (WAKO, Osaka, Japan) and were diluted in complete cell culture media to obtain concentrations from 5 to 30 µM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to colon cancer cells, in breast cancer cells, compound 24b upregulated only p21 in the p53-wildtype MCF-7 cells, while T47D cells (p53 L194F ) treated with compound 24b showed no p21 changes but activation of PARP1, albeit compound 24b inhibited the mortalin-p53 interaction in both cell lines [ 101 ]. More recently, compound 24c ( Figure 4 , mortaparib mild ) was identified as an inhibitor of PARP1 and mortalin-p53 interaction in HCT-116 cells, however, at higher concentrations than compounds 24a and 24c , thus leading to the attribute “mild” for compound 24c [ 102 ].…”
Section: Hsp70 Inhibitorsmentioning
confidence: 99%